On strongly FÎ²p-irresolute mappings - Kumar Saraf, Ratnesh; Caldas, Miguel (CUBO, A Mathematical Journal, 2011)
In this paper, we introduce a new class of mappings called strongly FÎ²p-irresolute mappings between fuzzy topological spaces. We obtain several characterizations of this class and study its properties and investigate the relationship with the known mappings.